Fire in Paradise: Why the Pantanal is burning. Issue 123 (September 2021) - Leal Filho, Walter; Azeiteiro, Ulisses M.; Salvia, Amanda Lange; Fritzen, Barbara; Libonati, Renata
Highlights: The Pantanal, the largest continental wetland in the world, is facing severe fires. These events are a combination of changing climate and human activities. This communication calls attention to the need for partnerships and improved monitoring. Abstract: This Communication reports on the fires recently seen in the Pantanal region, in Brazil, the largely continental wetland globally. It outlines the causes of the problem and some of the means which may be deployed to address them.